Why and when does multitasking impair flow and subjective performance? A daily diary study on the role of task appraisals and work engagement - Pluut, Helen; Darouei, Maral; Zeijen, Marijn Eveline Lidewij (Frontiers in Psychology, 2024)
In this diary study, we contribute to research on day-level multitasking in organizations by investigating why and when multitasking impairs employees’ work-related flow and subjective job performance on a daily basis. Drawing on Lazarus and Folkman’s transactional model of stress and coping, we propose that employees’ appraisal of their daily tasks (i.e., less challenging and more hindering) may explain why multitasking has negative implications for flow and job performance. Moreover, we expect that daily work engagement can buffer the detrimental effects of multitasking on flow and job performance. A total of 33 professional workers in the food industry participated in our study and were asked to respond to 10 daily surveys at work across 4 weeks. In line with our expectations, results showed that on days when employees’ working time was highly fragmented across a high number of tasks, they experienced less flow and, in turn, their job performance was lower on that particular day. Moreover, appraisal of daily tasks as less challenging – though not more hindering – explained why multitasking impairs flow. Finally, daily work engagement buffered the detrimental impact of multitasking on flow. The results presented in this paper offer novel and ecologically valid insights into why and when multitasking may backfire for employees.